Analisis Manajemen Pendidikan Tinggi: Studi Kasus Pada Universitas Widya Gama Mahakam Samarinda - Salim, Nur Agus (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research aims to analyze higher education management using a case study at Widya Gama Mahakam University, Samarinda. In this research, the author used a literature review or literature study method. Literature review is reviewing scientific literature on a topic and critically analyzing, evaluating, and synthesizing research findings, theory, and practice. It is hoped that the results of this research will provide a deeper understanding of higher education management and provide recommendations for further improvement and development.